Anatomy of Main Coronary Artery Location: Radial Position around the Aortic Root Circumference - Almuwaqqat, Zakaria; Tranquilli, Maryann; Elefteriades, John (International Journal of Angiology, 2012)
There is a relative dearth of fundamental anatomic information regarding the radial component of right and left coronary ostial location along the circumference of the aortic root. Recent literature has emphasized the importance of this anatomic component in the orientation of coronary buttons for the composite graft operation, especially as regards the use of porcine biological roots or design of novel mechanical or biological composite grafts. Problems in orientation of reattached buttons can lead to life-threatening ischemia. We assessed the radial location of native coronary arteries or coronary artery buttons by high-definition computed tomography scan in 100 patients (75 consecutive aneurysm patients undergoing aortic root replacement [ARR] and 25 control patients undergoing coronary artery bypass). We excluded six patients with unclear coronary anatomy and one with an anomalous origin. The center point of the aortic lumen was located, radii were drawn from there to each coronary ostium, and the angle was computed geometrically. The mean angle between the radii for the right and left coronary ostia was 122.9 degrees. The angle was similar for bicuspid and tri-leaflet aneurysm patients, 121.0 and 122.7 degrees, respectively. The angle was similar for aneurysm patients (121.6 degrees) and for controls (126.5 degrees). The angle showed very little variation among individuals for the overall group (standard deviation [SD] 13.1 degrees), for the aneurysm patients (SD 13.4 degrees), and for the controls (SD 12 degrees). This angle is different from that of the porcine roots (145 degrees) which are commonly used for ARR. The normal human angular separation between the right and left coronary ostia is 122.9 degrees for both aneurysm and control patients. This anatomic relationship is very different from that of porcine aortic roots. This anatomy needs to be borne in mind intraoperatively. This anatomic relationship can be used in the design of novel aortic root biological or composite grafts.
Keywords: aortic root replacement; coronary reimplantation; Medtronic FreeStyle; coronary angle